ANALISIS PENGARUH EARNING QUALITY DAN MARKET TO BOOK RATIO TERHADAP RETURN SAHAM ( Studi Pada Perusahaan Manufaktur Yang Terdaftar Pada Bursa Efek Indonesia) - Nafi’ Inayati Zahro; Wisnu Haryo Pramudya (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2014)
The purpose of this research is to analyse the effect of earning quality and market to book ratio on stock return. Using the sample of manufacturing companies listate in Indonesia Stock Exchange in the periode 2007-2010. The purposive sampling is used to collect 300 samples. The study fine that there is a positive effect of earning quality on stock return. The market to book ratio negatively affects stock return. Keywords: earning quality,market to book ratio, stock return, earnings response coefficients (ERC)